Enantioselective synthesis of 6,6-disubstituted pentafulvenes containing a chiral pendant hydroxy group - Nouch, Ryan; Cini, Melchior; Magre, Marc; Abid, Mohammed; Diéguez, Monserrat; Pàmies, Oscar; Woodward, Simon; Lewis, William (Wiley-VCH Verlag, 2017)
Simple enantioselective synthesis of 6,6-disubstituted pentafulvenes bearing chiral pendant hydroxy groups are attained by cascade reactivity using commercially available proline-based organocatalysts. Condensation of cyclopentadiene with the acetyl function of a 1,2-formylacetophenone, followed by cyclization of a resulting fulvene-stabilized carbanion with the formyl group, generates bicyclic chiral alcohols with initial er values up to 94:6. Exceptional enantio-enrichment of the resultant alcohols results upon crystallization – even near racemic samples spontaneously de-racemize. This enables new families of substituted cyclopentadienes that are both enantiomerically and diastereomerically pure to be rapidly attained.